2007
DOI: 10.1038/nature05956
|View full text |Cite
|
Sign up to set email alerts
|

Non-random coextinctions in phylogenetically structured mutualistic networks

Abstract: The interactions between plants and their animal pollinators and seed dispersers have moulded much of Earth's biodiversity. Recently, it has been shown that these mutually beneficial interactions form complex networks with a well-defined architecture that may contribute to biodiversity persistence. Little is known, however, about which ecological and evolutionary processes generate these network patterns. Here we use phylogenetic methods to show that the phylogenetic relationships of species predict the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
652
2
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 491 publications
(698 citation statements)
references
References 24 publications
33
652
2
11
Order By: Relevance
“…This nested structure has been claimed to be very stable to environmental and biotic stochasticity (Petanidou et al 2008) with low sensitivity to sampling effort (Nielsen & Bascompte 2007). However, the empirical evidence for plant-pollinator network stability in the face of global change is scarce, while most of it is based on models that simulate species removals (Memmott et al 2004;Rezende et al 2007) and habitat destruction (Fortuna & Bascompte 2006) as two main drivers of biodiversity loss. Even less explored are the effects of species introductions on network stability (but see Olesen et al 2002;Aizen et al 2008;Bartomeus et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This nested structure has been claimed to be very stable to environmental and biotic stochasticity (Petanidou et al 2008) with low sensitivity to sampling effort (Nielsen & Bascompte 2007). However, the empirical evidence for plant-pollinator network stability in the face of global change is scarce, while most of it is based on models that simulate species removals (Memmott et al 2004;Rezende et al 2007) and habitat destruction (Fortuna & Bascompte 2006) as two main drivers of biodiversity loss. Even less explored are the effects of species introductions on network stability (but see Olesen et al 2002;Aizen et al 2008;Bartomeus et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The concept was first proposed in the early twentieth century but only became popular among ecologists with its application to the biogeographic pattern of species occurrence in islands and other fragmented landscapes 1,2 . More recently, nestedness in species interaction networks has received significant attention [3][4][5][6][7] , where it has been suggested that a nested pattern of interactions leads to greater biodiversity in mutualistic systems such as plant-pollinator networks 8,9 . In a nested bipartite network or graph, interactions are organized such that specialists (for example, pollinators that visit few plants) interact with subsets of the species with whom generalists (for example, pollinators that visit many plants) interact.…”
mentioning
confidence: 99%
“…While the How each species interacts can be affected its evolutionary history (phenotypic traits; a). For example, closely related species might have a similar pattern of interaction, simply because of niche conservatism (Rezende et al 2007). Besides, the interaction pattern itself can be subject to the effect of both the animal and plant phylogenetic histories (b), with a marked trend for the interactions to match the phylogenetic history of the two groups (b, top), one of them (the plants in this case; b, middle) or none (b, bottom) Jordano and Bascompte, in prep palm is quite dependent on the toucan for successful fruit removal, the fruits are a minor part of the toucan generalist diet; in contrast, the jacutinga relies extensively on the palm fruits, but due to low abundance and infrequent visitation to the fruiting palms, it plays a secondary role as seed disperser.…”
Section: Mutual Benefits Antagonism and Who Eats Whom Complexitymentioning
confidence: 99%